Clean energy economy in the Russian far east ("Journal "U". Economy. Management. Finance.", 2024)
The article explores the prospects for the transition of the Russian Far East to a clean energy economy. It examines the main areas of renewable energy development in the region, such as hydropower, wind energy, solar energy, and geothermal sources. The challenges to the transition to clean energy are analyzed, including climatic and geographical constraints, financial barriers, and low population density. Special attention is given to government support and international cooperation, as well as the consideration of innovative solutions that could accelerate the development of renewable energy in the Far East. The economic and environmental benefits of transitioning to clean energy are discussed.
Keywords: clean energy; renewable energy sources; Russian Far East; energy transition; sustainable development; innovative technologies; government support; international cooperation; energy security; hydrogen energy